Self-testing for 5 respiratory viruses in adult VACCELERATE volunteers in Germany—a pilot study on multi-pathogen rapid antigen testing to monitor community-acquired acute respiratory infections - Nacov, Julia A.; Salmanton-García, Jon; Grimm, Sarah; Stewart, Fiona A.; Cremer, Louise M.; Rochel, Lisa Marie; Müller, Erik; Joisten, Carolin; Többen, Christina; Mechtel, Ben; Fleig, Julian; Bethe, Ullrich; et al. (Frontiers in Public Health, 2025)
BackgroundAcute respiratory infections (ARI) are the most common human infections. Diagnostic testing for respiratory pathogens is largely restricted to medical institutions. Self-testing may allow for real-time epidemiological monitoring of ARI pathogens, in particular in individuals not seeking medical attention.MethodsAdults from the VACCELERATE Volunteer Registry received a test-kit for multiple respiratory antigens, a laminar flow device (LFD) detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza viruses A and B, respiratory syncytial virus (RSV) and adenovirus (ADV) from a single nasal swab. During one winter season, participants self-tested upon ARI symptoms, reported LFD result as well as symptoms, vaccination history, and any underlying conditions. Participants who remained without ARI symptoms self-tested on the last day of the study period.ResultsBetween December 7, 2022, and June 2, 2023, 1,429 participants communicated their self-testing results. Of these 1,119 (78.3%) individuals had developed ARI symptoms and self-tested until May 31, 2023. Overall, 359 of 1,119 (32.1%) tests were positive with 17 (1.5%) co-detections, resulting in 377 detected pathogens overall. Thirteen tests (1.2%) were invalid or failed technically, and 747 (66.8%) were negative. The most frequently detected pathogen was SARS-CoV-2 (n = 178; 47.2%) followed by RSV (n = 109; 28.9%) and influenza A virus (n = 74; 19.6%). ADV was detected in 10 (2.7%) and influenza B virus in six (1.6%) samples only. Participants with detection of influenza A virus reported more often cough (91%), fever (59.7%), and myalgia (43.3%) than participants with detection of RSV or SARS-CoV-2. The remaining 310 participants (21.7%) who had not developed ARI symptoms self-tested on June 1, 2023, yielding an RSV point prevalence of 7.1%.ConclusionThis study allowed real-time reporting of five endemic ARI pathogens in a citizen science project. Symptom burden was highest in influenza A. Seasonal and off-seasonal RSV detection hint toward relevant RSV circulation in adults all year round.